2016
DOI: 10.3389/fimmu.2016.00656
|View full text |Cite
|
Sign up to set email alerts
|

Human NK Cell Subsets in Pregnancy and Disease: Toward a New Biological Complexity

Abstract: In humans, NK cells are mainly identified by the surface expression levels of CD56 and CD16, which differentiate between five functionally different NK cell subsets. However, nowadays NK cells are considered as a more heterogeneous population formed by various subsets differing in function, surface phenotype, and anatomic localization. In human CMV- and hantaviruses-infected subjects, an increased frequency of a NKG2A−CD57+NKG2C+ NK cell subset has been observed, while the phenotype of the NK cell subpopulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 54 publications
0
40
0
1
Order By: Relevance
“…− and express a repertoire of activating and inhibitory receptors (NKRs) that can fluctuate in response to EVT and invading pathogens [63]. Although the biological functions of uNK cells is still largely unknown, these cells appear to be important for spiral artery remodeling.…”
Section: Uterine Vascular Changes During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…− and express a repertoire of activating and inhibitory receptors (NKRs) that can fluctuate in response to EVT and invading pathogens [63]. Although the biological functions of uNK cells is still largely unknown, these cells appear to be important for spiral artery remodeling.…”
Section: Uterine Vascular Changes During Pregnancymentioning
confidence: 99%
“…In a healthy pregnancy, most dNKs are CD56 bright cells that possess granules such as perforin and granzyme B but have low potential for degranulation and are mainly pro-angiogenic, cytokine secreting and immunomodulatory. Double-negative or CD56 dim populations have been described as secreting low levels of IFN-γ and TNF-α and having a detrimental impact on pregnancy [63]. A number of studies have found that alterations in dNK subsets are higher in cases of unexplained recurrent miscarriage, infertility, and implantation failure [81][82][83][84].…”
Section: P Gingivalis As a Vascular Pathogen Of The Placental Bedmentioning
confidence: 99%
“…Notably, alterations in circulating NK cells frequency, phenotype and function have also been found in tumour patients and have been associated with the clinical outcome . So far, the analysis of peripheral blood NK cells in solid tumours patients showed an association between a suppressed functionally impaired NK cells phenotype and poor prognosis.…”
Section: Natural Killer Cells and Melanoma Immunotherapymentioning
confidence: 99%
“…80 Notably, alterations in circulating NK cells frequency, phenotype and function have also been found in tumour patients and have been associated with the clinical outcome. [81][82][83][84][85][86][87][88][89][90] So far, the analysis of peripheral blood NK cells in solid tumours patients showed an association between a suppressed functionally impaired NK cells phenotype and poor prognosis. Peripheral NK cells from metastatic melanoma patients show an exhausted phenotype, with a high expression of KIRs, low levels of NCRs and downregulation of stimulating cytokines receptors, that result in functional defects in their ability to proliferate, secrete cytokines and kill target cells.…”
Section: Cells and Melanoma Immunotherapymentioning
confidence: 99%
“…В ходе развития методов ис-следования оказалось, что данные популяции ге-терогенны и, в свою очередь, разделяются на не-сколько субпопуляций, способных выполнять как эффекторные, так и регуляторные функции. Нарушение баланса между этими субпопуля-циями происходит при многих заболеваниях, в том числе онкологических [7]. При изуче нии иммунофенотипа линейных популяций лимфо-цитов периферической крови первичных боль-ных раком яичников до и после хирургического лечения было обнаружено, что происходит на-рушение линейности, то есть у таких больных снижено количество Т-лимфоцитов по сравне-нию с контрольной группой доноров (62,5±3,1 и 73,9±2,5% соответственно), в том числе за счет повышения количества NK-лимфоцитов [4].…”
Section: Introductionunclassified